Studi Kelayakan Finansial Dan Teknis Proyek Pembangunan Sadira Plaza Pekanbaru - Afif Ramda; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Nowadays, development of shopping centres in Pekanbaru is rapidly growing. Cause of high capital cost, the investment in shopping centre is a risky business. Therefore, technical and financial analysis of construction compulsory. Technical aspect which is the parking space requirements and financial aspects which are calculations of Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return, Payback Period (PBP) and Sensitivity have been carried out. The result shown that available parking space of 188 SRP is smaller than Dirjen Perhubungan Darat’s standard of parking space requirements that 279 SRP. In other words, it only can accommodate 67% of standard of parking space requirements. Total investment of Sadira Plaza is Rp 167,530,104,997.76 in which Rp 83,477,913,329.51 of NPV, 1.32 of BCR and eight years and eight months of PBP (50 years of estimated project lifetime). In conclusion, investment in Sadira Plaza construction project is eligible to be built with a minimum tenant of 42.95% while technically not. Keywords: Technical Analysis, Financial Analysis, Sensitivity Analysis, Sadira Plaza, Pekanbaru